Penerapan Sistem Akuntansi Penjualan Produk dan Jasa pada UKM Bengkel Arm26 - Farrouk, Sulthon (PT. Alahyan Publisher Sukabumi, 2025)
This study aims to analyze the implementation of an accounting system for product and service sales at UKM Bengkel ARM26. The main issue faced by the business is the absence of a systematic financial recording system that aligns with accounting principles. This research uses a descriptive qualitative approach with data collected through observation, interviews, and documentation. The designed accounting system utilizes Microsoft Excel and includes account classification, general journal, ledger, income statement, and balance sheet. The results show that the implemented system is capable of recording transactions in a structured manner and generating more accurate financial reports. The reported income and profit after system implementation are more realistic due to the inclusion of all cost components. The system also enables the business owner to monitor financial performance and prepare financial reports that support decision-making and external needs such as loan applications. These findings indicate that a simple accounting system based on Excel can be an effective solution for small enterprises with limited resources and no formal accounting system in place.